The implementation of learning organization elements and their impact towards organizational performance amongst NPOs in Singapore - Md. Som, Hishamuddin; Roland, Yeow Theng Nam; Nordin, Rashid; Ajis, Mohd Na'eim; Keling, Mohamad Faisol; Shuib, Md. Shukri (Far East Research Centre, 2011)
The purpose of this paper is to investigate how Learning Organization Elements (LOE) was implemented amongst non-profit human social service organizations in Singapore. Through a self-administered survey and in-depth interviews, organizational performances of 60 non-profit organizations NPOs were evaluated, whilst the extent to which the LOE were carried out within these NPOs were also discussed. Specifically, elements such as clarity of mission and vision, experimentation and intrinsic motivation, leadership commitment and empowerment, and organizational learning practices were deemed to be essential for NPOs in Singapore to be transformed into a learning organization. In addition, individual learning and team-problem solving and organizational learning practices were also mentioned by the interviewed respondents as important elements toward NPOs‟ performance.Implications of the study including the applications of those LOE together with a strategic dimension in order for NPOs to become learning organizations, as well as to achieve superior organizational performance were also highlighted.